Pengaruh Strategi Pembelajaran Reciprocal Learning dan Think Talk Write Terhadap Hasil Belajar dan Retensi Siswa Pada Mata Pelajaran IPA Biologi Kelas VIII SMP Negeri 1 Sambi Tahun Pelajaran 2015/2016 - Muliyana, Riska (2016)
Learning success is aqualified indicator of education. Learning success is measured by how long the students's mastery the concepts they have learnt. Retention's factor in the concept of memory have a less attention. Learning is not measured in the mastery of concepts only, but it should be analyzed about what the concepts have learnt, it can be closed with student's memories or quickly forgotten. The objectives of this study are to assess the effect of reciprocal learning and learning strategies of talk think write face on learning outcomes and student's retention in science subjects in class VIII at SMP Negeri 1 Sambi in academic year 2015/2016.This research employs a quasi-experimental research, research design The Nonequivalent Control Group Design. The technique of collecting data are used documentation and test. Result of the data is analyzed by using Paired Sample T Test, One Way Anova and Multivariate. The results showed that reciprocal learning group consisting of 69.48and student's retention consisting of 63.12 with a difference of 6.35 from the postest value, the group of talk think write consisting of 79.03, the mean of student's retention about 67.5 with a difference of 11.53 from the postest value, and the control group (speech) it consists of learning outcomes about 70.31 and the student's retention about 14.38 with a difference of 55.93 from the postest value. From this research can be concluded that the learning strategy talk think write has greater impact on learning outcomes of biological science, reciprocal learning has greater impact on student's retention. Keywords: reciprocal learning, talk think write, learning outcomes, retention